Biocontrol potential of indigenous entomopathogenic nematodes from Cameroon against scale insect pest Stictococcus vayssierei and tending ant Anoplolepis tenella - Kanga, F.N.; Hauser, S.; Moens, M. (Elsevier, 2020)
In a 3-step approach, three series of experiments were carried out to assess the virulence and environmentally-dependent biocontrol potential of entomopathogenic nematodes from Cameroon against two cassava insect pests, Stictococcus vayssierei and its trophobiotic ant, Anoplolepis tenella, under laboratory and screenhouse conditions. In the first series, 20 isolates (18 Heterorhabditis baujardi, 1 Steinernema cameroonense, and 1 S. nyetense) were separately checked for their ability to infect the two pests at a rate of 500 infective juveniles (IJs)/insect for 36 h, and to select the most virulent isolates. All isolates were pathogenic to both pests, and caused 10% to 90% and 0 to 63% mortality of S. vayssierei and A. tenella, respectively. In a second series of virulence bioassays, 2 sets of 4 selected isolates were examined for: (a) concentration-response, (b) time-response, and (c) reproduction. Stictococcus vayssierei mortality ranging from 56 to 62% were observed at doses of 75–100 IJs/insect within 24–36 h. Nematodes at doses of 100–500 IJs/insect caused 51% mortality within 36 h. Nematodes successfully reproduced in both pests. The third bioassay series investigated migration and host preference abilities of selected isolates as well as nematode attachment to ants. The dispersal of IJs as affected by soil moisture and soil type was studied under screenhouse conditions. Nematodes exhibited positive attraction to both pests, yet with no preferential movement of IJs. Nematode dispersal and persistence (up to 89 days) were favored in sandy clay loam soils at pF 3.5 and pF 4.2 (9–15% moistures). The results from this study are sufficiently encouraging to embark on in situ testing. For integrated S. vayssierei control, implications such as the development of an adequate field application method to be used at field conditions are discussed, as even moderate levels of control might be economically profitable.